Kadar kelarutan fluor Glass Ionomer Cement setelah perendaman air sungai dan akuades - Phradina Fili Septishelya; Muhammad Yanuar Ichrom Nahzi; Nurdiana Dewi (Majalah Kedokteran Gigi Indonesia, 2016)
The Level of Fluor Solubility of Glass Ionomer Cement after submergence in the river water and aquadest GIC (GIC) is a restoration material that has a number of adhesive characteristics, tooth-coloured, and can release fluoride ion influenced by pH. The river water of Anjir Pasar village has acidic nature with pH as low 3. Acid pH can increase Fluor ion solubility in GIC. The aim of the study was to find difference of fluor ion solubility of GIC after submergence in the river water and aquadest. This study used GIC samples with the diameter of 5 mm and thickness of 2 mm. One group was soaked in river water and another group was soaked in aquadest for 7 days before conducting the measurement of the fluor ion solubility. The data were analysed by parametric Independent T-Test 95% (α=0.05) and it was found p value = 0.002 (p<0.05). The result indicated a significant difference of fluor ion solubility between GIC after submergence in river water and aquadest. It can be concluded that there is a significant difference of fluor ion solubility of GIC in which submergence in the river water was found higher than that of aquadest.ABSTRAKGlass Ionomer Cement (GIC) merupakan bahan restorasi yang memiliki sifat adhesif, sewarna dengan gigi dan memiliki kemampuan pelepasan ion fluor yang dipengaruhi derajat keasaman (pH). Air sungai Desa Anjir Pasar memiliki sifat yang asam dengan pH 3. Derajat keasaman (pH) asam dapat meningkatkan kadar kelarutan ion fluor pada GIC. Tujuan penelitian ini untuk mengetahui perbedaan kadar kelarutan ion fluor pada GIC setelah perendaman dalam air sungai Desa Anjir Pasar dan akuades. Penelitian ini menggunakan sampel GIC dengan diameter 5 mm dan ketebalan 2 mm. Masing-masing kelompok direndam dalam air sungai dan akuades selama 7 hari kemudian dihitung kadar kelarutan ion fluornya. Data diuji menggunakan analisis parametrik Independent T-Test 95% (α=0,05) dan didapatkan p=0,002 (p<0,05). Dari hasil tersebut diketahui bahwa terdapat perbedaan bermakna antara kadar kelarutan ion fluor setelah perendaman air sungai dengan kadar kelarutan ion fluor setelah perendaman akuades. Disimpulkan bahwa terdapat perbedaan yang signifikan antara kadar kelarutan ion fluor pada GIC setelah perendaman dalam air sungai Desa Anjir Pasar Barito Kuala yang lebih tinggi daripada setelah perendaman dalam akuades.